Analysis Of the Ministry of ATR/BPN Employee Scholarship Program in The Framework of The Realization of The Concept of Walfare State of The United State of The Republic of Indonesia - Setiawan, Agung; Umam, Khairul; Amalia, Riska Ari; Rahmadani, Rahmadani (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2024)
The Welfare State ideology teaches about the role of the State which is broader than the "night watchman", The ideals of the welfare state which have been stated in the 1945 Constitution are continued with the existence of Law number 20 of 2023 concerning the State Civil Apparatus (ASN). ASN of the Ministry of ATR/BPN has issued Scholarships for employees as a form of employee and institutional welfare. The study uses the statue approach which shows that the efforts of the Ministry of ATR/BPN in realizing the welfare state have been seen, only the educational qualifications are still for certain education, in fact every ASN has the same opportunity to get a scholarship according to the Utrecht Welfare State theory.